(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
to familiarize students with the basics of industrial toxicology, the effects of industrial poisons on the body of workers and measures to prevent occupational diseases and poisoning, as well as to give an idea of sanitary and chemical methods for determining the content of harmful chemical substances (HCS) in the air; teach how to give a hygienic assessment of chemical air pollution.